Dementia-linked amyloidosis is associated with brain protein deamidation as revealed by proteomic profiling of human brain tissues - Adav, Sunil S. (Mol Brain, 2016)
BACKGROUND: Aggregation of malformed proteins is a key feature of many neurodegenerative diseases, but the mechanisms that drive proteinopathy in the brain are poorly understood. We aimed to characterize aggregated proteins in human brain tissues affected by dementia. RESULTS: To characterize amyloidal plaque purified from post-mortem brain tissue of dementia patient, we applied ultracentrifugation-electrostatic repulsion hydrophilic interaction chromatography (UC-ERLIC) coupled mass spectrometry-based proteomics technologies. Proteomics profiling of both soluble and aggregated amyloidal plaque demonstrated significant enrichment and deamidation of S100A9, ferritin, hemoglobin subunits, creatine kinase and collagen protein among the aggregated brain proteins. Amyloidal plaques were enriched in the deamidated variant of protein S100A9, and structural analysis indicated that both the low- and high-affinity calcium binding motifs of S100A9 were deamidated exclusively in the aggregated fraction, suggesting altered charge state and function of this protein in brain tissues affected by dementia. The multiple deamidated residues of S100A9 predicts introduction of negative charge that alter Ca(++) binding, suggesting increased capacity to form pathological aggregates in the brain. CONCLUSION: UC-coupled proteomics revealed that brain amyloidal plaques are enriched in deamidated proteins, and suggested that altered charge state and calcium-binding capacity of S100A9 may enhance protein aggregation and promote neurodegeneration in the human brain. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13041-016-0200-z) contains supplementary material, which is available to authorized users.